Using Wordtune as an AI-Powered Writing Tool How is the Performance in Rewrite and Rephrase English Writing? - Fitria, Tira Nur (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
This research describes the use of Wordtune as an AI-Powered writing tool for rewriting or rephrasing English writing. This research uses descriptive qualitative research. The analysis shows that Wordtune can be accessed at www.wordtune.com. If we do not have an account, we can register by using Google, Apple, Facebook, and Email, then we can log in. We answer questions related to writing needs and choose our profession and native language. In an initial trial, we can use Wordtune in a free version. We can input the sample sentences or text in the column available. Several alternative writing options including Rewrite, Casual, Formal, Shorten, and Expandâ€ will be generated, then we choose one of them. Wordtune gives us several options to adjust to our writing style including casual, formal, short, or expand. Rewrite is exploring new ways to rephrase our sentences. Casual is conveying a lighter and less serious tone for the right audience. Formal is presenting sentences in a more sophisticated and professional way. Shortening is sticking to word limits and conveying messages clearly and concisely. Expanding is expanding our sentences to give more detail, nuance, and depth. We as educators need to teach students how to use this AI text writer wisely and responsibly. Students can use it to help improve the clarity and style of their writing. However, every writing produced by AI certainly needs to be checked for accuracy because AI tools may produce results that are inconsistent with readability and meaning.